Observation of intrinsically bright terrestrial gamma ray flashes from the Mediterranean basin. Issue 23 (14th December 2015) - Gjesteland, T.; Østgaard, N.; Laviola, S.; Miglietta, M. M.; Arnone, E.; Marisaldi, M.; Fuschino, F.; Collier, A. B.; Fabró, F.; Montanya, J.
Abstract: We present three terrestrial gamma ray flashes (TGFs) observed over the Mediterranean basin by the Reuven Ramaty High Energy Solar Spectroscope Imager (RHESSI) satellite. Since the occurrence of these events in the Mediterranean region is quite rare, the characterization of the events was optimized by combining different approaches in order to better define the cloud of origin. The TGFs on 7 November 2004 and 16 October 2006 came from clouds with cloud top higher than 10–12 km where often a strong penetration into the stratosphere is found. This kind of cloud is usually associated with heavy precipitation and intense lightning activity. Nevertheless, the analysis of the cloud type based on satellite retrievals shows that the TGF on 27 May 2004 was produced by an unusual shallow convection. This result appears to be supported by the model simulation of the particle distribution and phase in the upper troposphere. The TGF on 7 November 2004 is among the brightest ever measured by RHESSI. The analysis of the energy spectrum of this event is consistent with a production altitude ≤12 km, which is in the upper part of the cloud, as found by the meteorological analysis of the TGF‐producing thunderstorm. This event must be unusually bright at the source in order to produce such a strong signal in RHESSI. We estimate that this TGF must contain ∼3 × 10 18 initial photons with energy >1 MeV. This is 1 order of magnitude brighter than earlier estimations of an average RHESSI TGF. Key Points: We present meteorological conditions for TGF over the Mediterranean The TGFs come from cloud with high and shallow convection One of the TGF is estimated to be very bright at source